Governance and the Processes of Inclusion/Exclusion: A Review of the Theory and Practice - Alessia Ruggiero (European Regional Science Association (ERSA), 2006)
Governance identifies a discursive domain(Newman, 2002) in which both the policy and academic debate about new institutional configurations emerging from the proliferation of new forms of governing outside and beyond the state, is taking place My concern here is to highlight what I think is an under-theorised dimension in most of the perspectives from which the new forms of governance beyond the state are analysed. Specifically, I embrace Newman's (2001) suggestion that most of the literature on Governance suffers from an under-theorisation of a "social" dimension of the analysis or, of what she terms the "politics of the wider public realm and the patterns of inclusion and exclusion on which it is based." Using the above reflection as analytical starting point, this paper aims at showing how an important challenge for the field of Governance studies resides in the attempt to connect administrative and managerial issues with a broader set of issues concerning the nature of political participation in complex societes where not only the borders of the national states are blurred but the character of individual and collective identities is also relational and fluid. We will proceed first by critically reviewing from this perspective some of the current debates taking place in the Governance literature. Secondly by highlighting the concepts I consider fruitful to problematise the social dimension of the state-citizen relationship and to raise important questions with respect to the inclusionary and exclusionary practices on which it is based. And finally I will address the themes of inclusion and composition of consensus amidst diversity and complexity in the light of New Labour's approach to Governance and, specifically, of its discourses of social inclusion, democratic renewal, networks and partnership governing.
Keywords: 330